Evaluasi Kebijakan Lingkungan untuk Menilai Dampak Kebijakan terhadap Kelestarian Lingkungan - Marchelia indriyani; Dwi Handayani; Herlina Herlina (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
Environmental crises such as climate change, ecosystem degradation, and pollution have prompted countries to formulate environmental policies aimed at preserving environmental sustainability. However, the effectiveness of these policies is often questioned, particularly in their implementation. This article aims to evaluate the impacts of environmental policies implemented over the past decade on biodiversity, air quality, and waste management, as well as to identify implementation barriers and provide recommendations for policy improvement. The study employs a literature review method by analyzing various scientific sources, policy reports, and related documents. The evaluation results indicate that economic incentive-based policies, such as carbon taxes and renewable energy subsidies, tend to be more effective in reducing emissions and promoting clean energy adoption. Nevertheless, policy implementation frequently faces obstacles including lack of political support, limited resources, public resistance, and weak inter-sectoral coordination. Improvement strategies are needed, including enhanced cross-sector collaboration, strengthened data and information systems, and public education to support the success of sustainable environmental policies.